2023
DOI: 10.3389/fnut.2023.1137371
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sarcopenia in patients with COPD through different musculature measurements: An updated meta-analysis and meta-regression

Abstract: AimChronic obstructive pulmonary disease (COPD) patients vary widely in terms of the prevalence of sarcopenia, which is partially attributed to differences in diagnostic criteria and disease severity. There are several different musculature measurements that are used to quantify sarcopenia. This study included published literature for meta-analysis to assess the sarcopenia prevalence in COPD patients and correlate the disease with the clinical characteristics of such patients.MethodsA comprehensive review of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…Recent meta-analyses conducted by Sepúlveda‐Loyola et al and He et al reported prevalence rates ranging from 15.5 to 34% in the examined studies. These findings suggest a higher prevalence of sarcopenia in patients at advanced disease stages and its association with poorer pulmonary function and exercise capacity 24 , 25 . Martínez‑Luna et al demonstrated a strong association between low muscle mass and poor spirometry results, particularly in FEV 1 and FVC 26 .…”
Section: Discussionmentioning
confidence: 81%
“…Recent meta-analyses conducted by Sepúlveda‐Loyola et al and He et al reported prevalence rates ranging from 15.5 to 34% in the examined studies. These findings suggest a higher prevalence of sarcopenia in patients at advanced disease stages and its association with poorer pulmonary function and exercise capacity 24 , 25 . Martínez‑Luna et al demonstrated a strong association between low muscle mass and poor spirometry results, particularly in FEV 1 and FVC 26 .…”
Section: Discussionmentioning
confidence: 81%
“…Other important factors contribute to heterogeneity of patients. These comprise the ability to tolerate high stimulation intensities, muscle mass, deconditioning and sarcopenia [ 49 ] or cachexia. Still, they are not deeply investigated or reported by the authors, although deserving attention.…”
Section: Meta-analysis On Nems In Copd Patientsmentioning
confidence: 99%
“…All patients who were aged 18 years or older and diagnosed with RA according to the 1987 American College of Rheumatology (ACR) revised criteria [18] or the 2010 ACR/European League Against Rheumatism (EULAR) criteria [19], were consecutively recruited. Patients were excluded if they couldn't stand, walk, or perform handgrip strength by themselves, had overlap syndrome with other rheumatic or autoimmune disorders and vasculitides, had other risk factors for sarcopenia, e.g., chronic obstructive pulmonary disease [5,[20][21][22], end stage liver disease [6], neuromuscular disease, or had a metallic device implanted that might interfere with the body impedance analyzer interpretation. All participants were required to provided their informed consent prior to enrollment.…”
Section: Study Populationmentioning
confidence: 99%